Knowing "the Roma": Visual technologies of sorting populations and the policing of mobility in Europe. (August 2019) - Plájás, Ildikó Z; M'charek, Amade; van Baar, Huub
This paper examines ways of knowing "the Roma" as a category of people. It attends to mobility and its obstructions, and the ways that coincide with bureaucratic, institutional, and everyday modes of sorting and racializing groups of people. Our case study is situated in Romania. Whereas "the Roma" do not exist as a category in the Romanian national registry of citizens, mainstream public discourses regarding "Roma migration" have significantly proliferated over the past decades. Yet, how do authorities come to know "the Roma" and how do they render groups of citizens into racialized populations? We examine two bureaucratic practices in Romania, the census and the registry of citizens, and show how the latter is enacted through various "technologies of vision." We focus on the category of "the Roma" as a material semiotic configuration enacted by various "data" regarding issues such as territorial segregation, phenotypic appearance, smell, and dialect. Situated at the intersection of Border and Surveillance Studies, Romani Studies, and Science and Technologies Studies, this paper contributes to debates about how "the Roma" are rendered visible in practices of identification and migration management in Europe.